Pengaruh Pemberian Trichoderma sp. sebagai Dekomposer Berbagai Limbah Pertanian Terhadap Lama Pengomposan dan Kualitas Kompos yang Dihasilkan - Anik Khoiriyah; Ahmad Ilham Tanzil; Wildan Muhlison; Ummi Sholikhah (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2025)
The high productivity of rice, banana and coffee crops in Jember Regency results in high levels of straw, banana stalks and coffee skin waste. These wastes require further processing as organic fertilizer. However, natural composting of waste takes a long time so it requires the addition of a decomposer, Trichoderma sp. which can accelerate waste composting. This research was conducted at the Academic Support Unit. Agrotechnology Garden, University of Jember and Soil Chemistry Laboratory, Faculty of Agriculture, University of Jember from August to September 2024 using a Factorial Complete Randomized Design (CRD), namely compost materials (banana stump, coffee peel, and straw) and the addition of decomposers, there were 6 treatments with 4 replications so that there were 28 experimental units. The data obtained were analyzed using Analysis of Variance (ANOVA), if there were differences in each treatment, then continued with the Least Significant Difference Test (LSD) at the 95% confidence level. Based on the results of the study, the application of Trichoderma sp. decomposer affects temperature, can increase N-total in banana and coffee peel compost, and also increase K-total in straw compost, then reduce C-Organic in coffee peel and straw compost, and reduce the C/N ratio of banana and coffee peel compost. The application of Trichoderma sp. affects the length of composting of coffee skin waste based on the chemical content of compost, which has a C/N ratio of 19.42% which has met the SNI.